Risk Aversion and Reservation Wages - Markus Pannenberg (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
This study examines the relationship between individual risk aversion and reservation wages using a novel set of direct measures of individual risk attitudes from the German Socio-Economic Panel (SOEP). We find that risk aversion has a significantly negative impact on the level of reservation wages. Moreover, we show that the elasticity of the reservation wage with respect to unemployment benefits is remarkably lower for risk-averse job seekers than for risk-loving job seekers. The results are consistent with an interpretation that risk-averse job seekers set their reservation wage levels sufficiently low, so that they accept almost every job offer.
Keywords: J64; J65; 330; Risk Aversion; Reservation Wages; Survey Data